Maternal serum endothelial cell-specific molecule-1 level and its correlation with severity of early-onset preeclampsia - Ovayolu, Ali; Karaman, Erbil; Turgut, Abdülkadir; Güler, Selver; Bostancıeri, Nuray (Taylor and Francis Ltd., 2020)
Preeclampsia (PE), the primary pathology of which is endothelial cell (EC) dysfunction, has long-lasting effects such as cardiovascular disease. Therefore, it was decided to investigate the maternal serum concentrations of EC-specific molecule-1 in patients with early-onset preeclampsia (E-PE). This study was conducted on 33 pregnant women with E-PE and 35 healthy pregnant women matched for gestational age. EC-specific molecule-1 level was measured using a commercially available enzyme-linked immunosorbent assay kit. The mean EC-specific molecule-1 concentrations were not significantly different between the groups (651.7 ± 632.2 pg/mL vs. 425.9 ± 263.0 pg/mL, p=.056). Among women with E-PE, the median EC-specific molecule-1 concentration did not differ significantly by disease severity (p=.115). EC-specific molecule-1 is not involved in the pathogenesis of E-PE. However, some studies in the literature report that EC-specific molecule-1 concentrations increased during the diagnosis of PE. Therefore, well-designed studies with a large sample are needed in cases of E-PE.Impact StatementWhat is already known on this subject? There is an increased risk of cardiovascular disease (CVD) in early-onset preeclampsia (E-PE) which is linked with endothelial dysfunction. Endothelial cell (EC)-specific molecule-1 stands out as an important marker in EC dysfunction related conditions such as preeclampsia. What the results of this study add? This study showed that EC-specific molecule-1 is not associated with the CVDs risk linked with endothelial dysfunction in E-PE. Additionally, there was also no significant relationship was detected between the severity of E-PE and EC-specific molecule-1 concentrations. What the implications are of these findings for clinical practice and/or further research? Endothelial cell-specific molecule-1 is not involved in the pathogenesis of E-PE. Moreover, advantageous and easy-to-measure markers are needed in larger sample studies to better understand the aetiology of E-PE. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Biomarker; cardiovascular diseases; endocan; endothelial cell activation; endothelial dysfunction; predict